Trichoderma na germinação de sementes e no desenvolvimento inicial com vermicomposto em hortaliças - Silva, Nayra Grazielle da (2018)
Brazil is the world's largest consumer of agrochemicals and technological advances in the area of plant production have not reduced its use and as a consequence there is a supply of contaminated food to the population. The present project will create subsidies to evaluate the effect of bioproduct based on Trichoderma harzianum in vitro and isolated cultivation and associated vermicompost in agronomic greenhouse in the germination, initial development and promotion of horticultural growth. In the first article, the treatments (T) doses of trichoderma were as follows: T1) 0,0; T2) 108; T3) 109; T4) 1010 UFC.L-1. After inoculation, the seeds were distributed over two sheets of filter paper moistened with sterile distilled water in the amount of 2.5 times the paper weight. Twenty seeds of each species were evenly distributed per treatment. After 72 hours, the number of germinated and non-germinated seeds was determined and, after 7 days, the number of seeds germinated, being also measured the length of the aerial part and root system and fresh and dry plantlets of the seedlings. In the second article, the treatments (T) containing substrate composed of a mixture of vermicompost and sandy soil, were the following according to the doses of the Ecotrich® bioproduct based on trichoderma: T1) 0,0; T2) 108; T3) 109; T4) 1010 UFC.L-1. After inoculation, the substrate was placed in germination trays, where three cherry tomato seeds were sown per cell, totaling 90 seeds per treatment. Twelve days after sowing, the number of emerged seedlings was counted and the thinning was performed, and one seedling per cell was maintained. At 30 days after sowing, the height, collecting diameter, chlorophyll a, b and total, fresh and dry root and shoot phytomasses, root volume and area, leaf area and foliar chemical analysis were evaluated. It was concluded that the doses of trichoderma used in the present study had an inhibitory effect on the germination of mustard, tomato and arugula seeds in an in vitro experiment. Seeds of watermelon presented increase in germination in the presence of trichoderma and tendency of increase of the parameter with the increase of the concentrations. The initial development of vegetables also presented inferior results when compared to the treatments without trichoderma. The growth of cherry tomato inoculated with trichoderma doses in agronomic greenhouse in association with vermicompost concentrations presented similar results to the treatments without trichoderma when in the presence of higher concentrations of the organic substrate.